Absence of susceptibility vessel sign and hyperdense vessel sign in patients with cancer-related stroke - Beyeler, Morin; Grunder, Lorenz; Göcmen, Jayan; Steinauer, Fabienne; Belachew, Nebiyat F.; Kielkopf, Moritz; Clénin, Leander; Mueller, Madlaine; Silimon, Norbert; Kurmann, Christoph; Meinel, Thomas; Bücke, Philipp; et al. (Frontiers in Neurology, 2023)
Background and aim: Identification of paraneoplastic hypercoagulability in stroke patients helps to guide investigations and prevent stroke recurrence. A previous study demonstrated an association between the absence of the susceptibility vessel sign (SVS) on brain MRI and active cancer in patients treated with mechanical thrombectomy. The present study aimed to confirm this finding and assess an association between the absence of the hyperdense vessel sign (HVS) on head CT and active cancer in all stroke patients. Methods: SVS and HVS status on baseline imaging were retrospectively assessed in all consecutive stroke patients treated at a comprehensive stroke center between 2015 and 2020. Active cancer, known at the time of stroke or diagnosed within one year after stroke (occult cancer), was identified. Adjusted odds ratios (aOR) and their 95% confidence interval (CI) for the association between the thrombus imaging characteristics and cancer were calculated using multivariable logistic regression. Results: Of the 2256 patients with thrombus imaging characteristics available at baseline, 161 had an active cancer (7.1%), of which 36 were occult at the time of index stroke (1.6% of the total). The absence of SVS was associated with active cancer (aOR 3.14, 95% CI 1.45-6.80). No significance was reached for the subgroup of occult cancer (aOR 3.20, 95% CI 0.73-13.94). No association was found between the absence of HVS and active cancer (aOR 1.07, 95% CI 0.54-2.11). Conclusions: The absence of SVS but not HVS could help to identify paraneoplastic hypercoagulability in stroke patients with active cancer and guide patient care.